A wideband circularly-polarized spiral antenna for CubeSat application - Ahmad Mustafa, Ahmad Mujahid; Mohamad, Sarah Yasmin; Abdul Malek, Norun Farihah; Mohd. Isa, Farah Nadia; Islam, Md. Rafiqul (2017)
In this paper, a wideband circularly-polarized spiral antenna is proposed to be used for CubeSat application. The antenna covers two of CubeSat frequencies; the S-band (2.2 GHz) and X-band (8 GHz). The proposed antenna belongs to the wideband and frequency-independent antenna category, which are known to provide a constant radiation pattern, impedance and polarization throughout the whole bandwidth. The performance of the spiral is compared in two different conditions; in free space and above a ground plane with a separation distance of λ/4 at the operating frequency of 2.2 GHz and 8 GHz. The spiral above the ground plane exhibits a unidirectional radiation and higher gain with an increase of 26.6% (2.2 GHz) to 34.6% (8 GHz) than the free space spiral. Moreover, the return loss also managed to stay within the ideal limit of S11<-10dB (-19.528 dB at 2.2 GHz, and -21.92 dB at 8 GHz) and exhibits circularly-polarized radiation with low axial ratio < 3 dB (0.78 dB at 2.2 GHz, and 0.89 dB at 8 GHz).